If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + 12 + -1x = 9 + 3x + -7 Reorder the terms: 12 + 2x + -1x = 9 + 3x + -7 Combine like terms: 2x + -1x = 1x 12 + 1x = 9 + 3x + -7 Reorder the terms: 12 + 1x = 9 + -7 + 3x Combine like terms: 9 + -7 = 2 12 + 1x = 2 + 3x Solving 12 + 1x = 2 + 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. 12 + 1x + -3x = 2 + 3x + -3x Combine like terms: 1x + -3x = -2x 12 + -2x = 2 + 3x + -3x Combine like terms: 3x + -3x = 0 12 + -2x = 2 + 0 12 + -2x = 2 Add '-12' to each side of the equation. 12 + -12 + -2x = 2 + -12 Combine like terms: 12 + -12 = 0 0 + -2x = 2 + -12 -2x = 2 + -12 Combine like terms: 2 + -12 = -10 -2x = -10 Divide each side by '-2'. x = 5 Simplifying x = 5
| 4x-(x-7)=10 | | 12=2t+6-14 | | x^3+4x^2-5x-20=0 | | 6=11v-5v | | 3=2187 | | 63=4v+3v | | -5-16+16=9 | | 45=11-2j+50 | | -4(-8y+5)-7y=7(y-3)-2 | | 45=112j+50 | | 5(4.5+0.5y)-2=18 | | 2x-7=1x+9 | | (-6c+5)-(-3c+8)= | | 8y^2+2y-36=0 | | 4(x-1)=10x+20 | | 8y+2y-36=0 | | -40-7+9x=14 | | 3y+2y=4 | | f(x)=10x-2 | | 18x+9=5x+100 | | f(x)=10x-2graph | | 5x-2(-2x-9)=18 | | Y-6=-1(x+7) | | -25=87-8x | | (3x^2+2x)+(3x^2-2x)= | | f(x)=2x-4graph | | 3(x+4)-x=24+x | | t-2=-3t+4 | | Y-8=-1(x+12) | | 1/3*2/5=34 | | 60=3x-2y | | 3(-1)+4(-1+3)=5 |